2007
DOI: 10.1088/0268-1242/22/5/009
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the 100 MeV Au7+ion irradiation of GaN

Abstract: Metal organic chemical vapour deposition (MOCVD) grown n-type GaN on sapphire substrates was irradiated with 100 MeV Au 7+ ions, varying the fluence as 1 × 10 12 , 1 × 10 13 and 5 × 10 13 ions cm −2 at room temperature. The irradiated samples were characterized by x-ray diffraction (XRD), atomic force microscopy (AFM), Raman scattering, photoluminescence and UV-visible optical absorption spectrum. XRD analysis reveals a huge lattice disorder for fluence beyond 1 × 10 13 ions cm −2 . This is observed from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…In addition, grazing incidence SHI irradiation [15][16][17] was applied in order to study the response of the GaN surface in particular. Possible compositional changes in this case were investigated by TOF-ERDA which is sensitive to a possible nitrogen loss which has been reported previously for this material [18][19][20]. Our results are interpreted in terms of the material changes predicted by the thermal spike model [21,22].…”
Section: Introductionsupporting
confidence: 72%
“…In addition, grazing incidence SHI irradiation [15][16][17] was applied in order to study the response of the GaN surface in particular. Possible compositional changes in this case were investigated by TOF-ERDA which is sensitive to a possible nitrogen loss which has been reported previously for this material [18][19][20]. Our results are interpreted in terms of the material changes predicted by the thermal spike model [21,22].…”
Section: Introductionsupporting
confidence: 72%
“…In Fig. 4, the intensity of the different Raman bands after a given dose I(D), normalized to the intensity of this peak for unirradiated sample Io is plotted as log 10 FT-IR studies have been carried out to confirm the surface amorphisation. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This shift is an indicative of an evolution towards a highly disordered material. Suresh Kumar et al [10] have studied GaN using 100 MeV Au 7+ ion irradiation by varying the fluences 1 × 10 12 to 5 × 10 13 ions/cm 2 at room temperature. The structural studies were investigated using XRD and Raman scattering measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This shift is associated with the nitrogen loss that occurs upon irradiation [6]. This indicates that the lattice damage is high at LT irradiation as compared to RT irradiation.…”
Section: Raman Studiesmentioning
confidence: 93%
“…Previous reports [4,5] have indicated that GaN is very resistant to amorphisation and there exist a dose range of disorder saturation during irradiation. Recently our group reported that the lattice disorder has been observed after 100 MeV Au 7+ ions irradiation effects of GaN [6]. Irradiation in GaN at 15 K indicates a pronounced recombination of the defects produced within the primary collision cascades [7].…”
Section: Introductionmentioning
confidence: 98%